2017
DOI: 10.1021/acsomega.7b01185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Composition on the Microbehaviors of CH4 and CO2 in Slit-Nanopores: A Simulation Exploration

Abstract: Molecular dynamics simulation studies were employed to investigate the microscopic behaviors of CH 4 and CO 2 molecules in slit-nanopores (SNPs) with various surfaces and different compositions. Three kinds of SNPs were constructed by a pair-wise combination of graphene, silica, and the calcite surface. The grand canonical Monte Carlo and molecular dynamics simulation methods were used to investigate the adsorption and self-diffusion of the gases in the nanopores. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
5
16
0
Order By: Relevance
“…In the absence of water, both CO 2 and CH 4 show a layered structure on the calcite surface and the density profiles are symmetric with respect to the pore center ( Figure 3A). These density profiles indicate that CO 2 and CH 4 are adsorbed to create a single layer on the calcite surface in the absence of water which is consistent with previous studies (Franco et al, 2016;Sun et al, 2017;Wang et al, 2017;Simoes Santos et al, 2018). The higher density of CO 2 at the interface compared to CH 4 is attributed to the higher energetic affinity of CO 2 on the calcite interface compared to CH 4 as reported by Wang S. et al (2016b).…”
Section: The Structure Of the Confined Fluidssupporting
confidence: 90%
See 3 more Smart Citations
“…In the absence of water, both CO 2 and CH 4 show a layered structure on the calcite surface and the density profiles are symmetric with respect to the pore center ( Figure 3A). These density profiles indicate that CO 2 and CH 4 are adsorbed to create a single layer on the calcite surface in the absence of water which is consistent with previous studies (Franco et al, 2016;Sun et al, 2017;Wang et al, 2017;Simoes Santos et al, 2018). The higher density of CO 2 at the interface compared to CH 4 is attributed to the higher energetic affinity of CO 2 on the calcite interface compared to CH 4 as reported by Wang S. et al (2016b).…”
Section: The Structure Of the Confined Fluidssupporting
confidence: 90%
“…The diffusivity of CO 2 and CH 4 through calcite nanopores without water, one layer of interfacial water composed of 150 water molecules, 500 water molecules, and 1,296 water molecules to mimic the density of bulk water yielded interesting insights. In general, the diffusion coefficients of CO 2 and CH 4 in the absence of water are in reasonable agreement with Sun et al (2017) after accounting for the differences in temperature. The temperature used in this study is 298 K compared with 323 K studied by Sun et al (2017).…”
Section: Diffusivity Of Co 2 and Ch 4 Through Nanoporessupporting
confidence: 66%
See 2 more Smart Citations
“…It is found that, the Ds values of gases get enlarged with the pore size increasing at such range of pore size (∼5 Å–∼30 Å) . It can be found that, the Ds values of CO 2 are much smaller than N 2 , and comparing with self‐diffusion of CO 2 adsorbed in other slit‐nanopores, such as the nanopores of silica and montmorillonite, the Ds of CO 2 in calcite slit‐nanopore is much smaller, and in our previous work, we have also demonstrated that the CO 2 molecule has stronger adsorption capacity with the calcite surface than silica and graphene. While the self‐diffusion of N 2 in calcite slit‐nanopore is similar to that in carbon nanotubes (CNTs) and asphaltene nanopores, with the Ds values in the same order of magnitude, and which further indicates that the self‐diffusion of N 2 molecule is much larger comparing with CO 2 no matter in nanopores with organic matter or inorganic minerals.…”
Section: Resultsmentioning
confidence: 70%